2021
DOI: 10.3390/biom11070984
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Anti-Microbial Peptides (AMPs) against Leishmania and Other Parasites: An Overview

Abstract: Anti-microbial peptides (AMPs), small biologically active molecules, produced by different organisms through their innate immune system, have become a considerable subject of interest in the request of novel therapeutics. Most of these peptides are cationic-amphipathic, exhibiting two main mechanisms of action, direct lysis and by modulating the immunity. The most commonly reported activity of AMPs is their anti-bacterial effects, although other effects, such as anti-fungal, anti-viral, and anti-parasitic, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 154 publications
(187 reference statements)
0
14
0
Order By: Relevance
“…Antimicrobial peptides have broad-spectrum activity against gram-negative and gram-positive bacteria (64,65), fungi (66), eukaryotic parasites (67), and viruses (68) in vitro (69). Previous researchers demonstrated that antimicrobial peptides maintain the equilibrium of intestinal microecology by suppressing harmful pathogens and promoting proliferation of beneficial microorganisms in vivo, which improved intestinal health.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial peptides have broad-spectrum activity against gram-negative and gram-positive bacteria (64,65), fungi (66), eukaryotic parasites (67), and viruses (68) in vitro (69). Previous researchers demonstrated that antimicrobial peptides maintain the equilibrium of intestinal microecology by suppressing harmful pathogens and promoting proliferation of beneficial microorganisms in vivo, which improved intestinal health.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-leishmanicidal activity was observed in the Leishmania significant strain and exhibited a dose-dependent effect on promastigotes, in addition to demonstrating substantial effects on amastigotes [ 77 ]. As recently reviewed, the effectiveness of the members of the principal families of AMPs exhibiting a potential anti-leishmanial activity is discussed [ 78 ].…”
Section: Peptides With Cell-penetrating and Anti-infective Activity A...mentioning
confidence: 99%
“…In the absence of IL-32γ, the infection index increased, which was attributed to the decreased levels of iNOS/NO (nitric oxide) and antimicrobial peptides (β-defensin-2 and cathelicidin). Reactive oxygen intermediates (ROS) and antimicrobial peptides are reported to kill Leishmania ( 74 , 75 ). Accordingly, IL-32γ overexpression led to better parasite control together with increased production of microbicidal molecules ( Figure 1A ) ( 10 ).…”
Section: Il-32 In Different Leishmaniasesmentioning
confidence: 99%